Toleransi Antar Umat Beragama dalam Kerukunan Keluarga Masyarakat Seko di Desa Harapan - Sintikhe Pasombo; Abdul Rahman; Supriadi Torro (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to examine and analyze the socio-economic life of a pedicab driver in Losari Beach and adaptive strategies to meet their daily needs. This research is a qualitative research which is analyzed and written descriptively. Data collection techniques were carried out using the methods of observation, interviews, and documentation by involving 10 (ten) individuals as informants. The results of this study indicate that the socio-economic life of a pedicab driver on Losari beach is currently very worrying. This shows that the income as a pedicab driver in a day is not fixed. The distance traveled and the hours worked determine their income because the longer they work, the more likely they are to earn. The adaptive strategies of pedicab drivers on Losari beach in fulfilling their lives are decreasing with the presence of several types of public transportation such as online motorcycle taxis. The shift of customers from rickshaws to online motorcycle taxis is very detrimental to pedicab drivers. Adaptation strategies are essentially ways of survival that are carried out by everyone. This study aims to determine the form of tolerance that occurs in the family harmony of the Seko community in Harapan Village, Mappedeng District, North Luwu Regency, South Sulawesi Province as well as supporting factors for tolerance between religious communities in family harmony. the Seko community. This research uses descriptive qualitative research. The technique of collecting data that the author does in the field is the method of observation, interviews, and documentation. The results of this study indicate that the form of tolerance that occurs in the family harmony of the Seko community, namely: (a) Mutual cooperation, in terms of they work together in planting rice in the garden or what they often call Mambubu', (b) Maintaining the Silahtuhrahmi Rope, in terms of In this case they will visit each other when holding religious celebrations or parties, (c) Give freedom to practice religion, in this case each member is given the same right to practice religion according to their beliefs. The factors that support the occurrence of tolerance are (a) they are still in the same group, all KKMS members consider that they are all relatives who cannot be separated by anything, including the differences in their beliefs, (b) a strong understanding of the teachings of their respective religions, (c) there is an awareness of peaceful coexistence.uk can maintain its survival.